An Analysis of The Buddhist Ethics in Boon Samha Tradition at Pawainang Sub-District, Banfang District, Khonkaen Province - Kittipanyo, Phrakhru Kittibodhisan; bodhikun, Phrakhru Bhavana; Leeka, Jaras; Siridhammo, Phramahajaising; Siridhammo, PhramahaPaitool; Katasaro, Phramaha​Papon (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this research paper were 1) to study the concept of Buddhist ethics, 2) to study the Boon Sam Ha tradition of Pa Wai Nang Sub-district, Ban Fang District, Khon Kaen Province and 3) to study and analyze Buddhist ethics in the Boon Sam Ha tradition of Pa Wai Nang Sub-district, Ban Fang District, Khon Kaen Province. Is a qualitative research Study data from primary and secondary There were 30 key informants/person. The data were analyzed using the descriptive method according to the inductive method. The research results were as follows: 1. The Buddhist ethics, It is the principle of human conduct concerning good and evil, what should be done and should not be done, is the standard of human conduct in living for goodness. There is a criterion for judging goodness based on unwholesome roots (Kusala-mũla) or roots of good actions (generosity, love, wisdom) and evil based on unwholesome roots (Akusala-mũla) or roots of bad actions ( greed, hatred, delusion). 2. Boon Sam Ha is an important tradition of Pa Wai Nang Sub-district. This is a practice that has been passed down from the past to the present. with the belief that when making merit, this will make people and the animals in the village are happy and is a merit with relatives to show gratitude to the spirits of the ancestors with the ultimate goal of Nirvana. 3. Principles of Buddhist ethics found in the Boon Samha tradition of Pa Wai Nang Subdistrict, Ban Fang District, Khon Kaen Province, namely 1) Principles of Puññakiriyà-vatthu the bases of meritorious action or grounds for accomplishing merit, 2) Principles of the Five Precepts; rules of morality and the five ennobling virtues; virtues enjoined by the five precepts 3) the quality of being a grateful person; gratitude; gratefulness. 4) bases of sympathy 4 and 5) states of conciliation ; virtues for fraternal living 6, The Buddhist ethics as mentioned above is a practice that is hidden in the ritual process that helps to create values for the quality of life of all people in Pa Wai Sit Subdistrict.